Effect of malate-oligosaccharide solution on aerobic abilities in endurance athletes - Junqiang, Q.; Meiyun, F.; Xu, Y.; Xiangjun, W.; Wei, G.; Ying, Z. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this investigation is to probe into the different influence malate ingestion on blood lactate and glucose kinetics during aerobic exercise athletes. The results showed that: 1. The athletes supplied with oligosaccharide solution and malate plus oligosaccharide solution performed the cycling to exhausted for a longer time; 2. Malate plus oligosaccharide solution have good effect on maintaining a higher blood glucose concentration during exercise, increasing blood lactate removal rate; 3. Malate plus oligosaccharide solution has good effect on keeping decreased level of serum GOT and GPT activities after exercise. We can conclude that supplement of malate plus oligosaccharide can accelerate the lactate removal after exhausted cycling, keep a higher blood glucose concentration during 45 min cycling exercise, and decrease the GOT and GPT activities after exercise.